Comportamiento agronómico del cultivo de cebolla blanca (Allium fistulosum l.) Con diferentes abonos orgánicos” en la unidad educativa Calazacón de Santo Domingo de los Tsáchilas, año 2014 - Ramìrez Salazar, Byron Patricio (2015)
This research was conducted at the Education Unit Calazacón, Santo Domingo de los Tsáchilas and whose geographical location is 1 ° 3 '18 "south latitude and 79 ° 25' 24 '' west longitude, at an elevation of 655 meters above the sea level. The treatments were 7; 3 doses of humus and 3 doses of water hyacinth plus a control. The highest level of organic fertilizer in the production of white onion in Calazacón Education Unit of Santo Domingo de los Tsáchilas was in treatment which was applied between 3 and 5 kg of vermicompost, it shows the best results when compared to other treatment. The agronomic performance of white onion in Calazacón Education Unit of Santo Domingo de los Tsáchilas, plant height treatment 2 (3 kg of humus). Number of leaves, treatment 1 (1 kg of humus), reached the highest number of leaves at 15 days (2.75 leaves); 30 days Treatment 2 (3 kg of humus) with 3.33 leaves; 45 days 3.83 leaves; 60, 75 and 90 days. In the economic analysis of the treatments under study, revenues were determined by the total production of each treatment and the selling price of the final product, establishing treatment 5 kg of humus, reported higher revenues with $ 158.50 and benefit cost ratio of 0.52.